Peri-therapeutic multi-modal hemodynamic assessment and detection of predictors for symptomatic in-stent restenosis after percutaneous transluminal angioplasty and stenting - Song, Xiaowen; Qiu, Hancheng; Yang, Shuo; Liu, Yuqi; Cao, Yong; Wang, Shuo; Zhao, Jizong (Frontiers in Neurology, 2023)
Backgrounds This study performed multi-modal hemodynamic analysis including quantitative color-coded digital subtraction angiography (QDSA) and computational fluid dynamics (CFD) to delineate peri-therapeutic hemodynamic changes and explore the risk factors for in-stent restenosis (ISR) and symptomatic ISR (sISR). Methods Forty patients were retrospectively reviewed. Time to peak (TTP), full width at half maximum (FWHM), cerebral circulation time (CCT), angiographic mean transit time (aMTT), arterial stenosis index (ASI), wash-in gradient (WI), wash-out gradient (WO) and stasis index were calculated with QDSA and translesional pressure ratio (PR) and wall shear stress ratio (WSSR) were quantified from CFD analysis. These hemodynamic parameters were compared between before and after stent deployment and multivariate logistic regression model was established to detect predictors for ISR and sISR at follow-up. Results It was found that stenting generally reduced TTP, stasis index, CCT, aMTT and translesional WSSR while significantly increased translesional PR. ASI decreased after stenting, and during the mean follow-up time of 6.48 ± 2.86 months, lower ASI (<0.636) as well as larger stasis index were corroborated to be independently associated with sISR. aMTT showed a linear correlation with CCT before and after stenting. Conclusion PTAS not only improved cerebral circulation and blood flow perfusion but also changed local hemodynamics significantly. ASI and stasis index derived from QDSA were proved to play a prominent role in risk stratification for sISR. Multi-modal hemodynamic analysis could facilitate intraoperative real-time hemodynamic monitoring and help the determination of the end point of intervention.